A memory of muskets : a Chloe Ellefson mystery - Ernst, Kathleen, 1959- (Ernst, Kathleen, 1959- Chloe Ellefson mystery., 2016)
Curator Chloe Ellefson is happily planning to spotlight home-front challenges and German immigrants at Old World Wisconsin's first Civil War reenactment, but her overbearing boss scorns her ideas and proposes staging a mock battle instead. And when a reenactor is found dead at one of the historic site's German farms, Chloe's boyfriend, cop Roelke McKenna, suspects murder. The more Roelke learns about reenacting, the more he fears that a killer will join the ranks. Then Chloe discovers a disturbing secret about Roelke's Civil War-era ancestors. Together they struggle to solve crimes past and present . . . before Chloe loses her job and another reenactor loses his life.